Evaluasi Penggunaan Antibiotik Pada Pasien Anak Rawat Inap Rsu Mitra Sejati - Nerly Juli Pranita Simanjuntak; Simran Kaur; Razoki Razoki (CV. ITTC INDONESIA, 2025)
Inappropriate use of antibiotics can lead to resistance and other negative impacts, especially in vulnerable groups such as children. Evaluation of antibiotic use is very important to ensure the effectiveness of therapy and avoid resistance. This study aims to evaluate the use of antibiotics in pediatric patients hospitalized at Mitra Sejati Hospital using the ATC/DDD method and 90% DU analysis. This study used a retrospective approach from the medical records of pediatric patients aged 1-18 years during October 2024 to February 2025. Based on the results of the study, it was found that the most widely used type of antibiotics was ceftriaxone (5,70 DDD/100 patient-days). While based on the results of 90% DU analysis, the most commonly prescribed antibiotics were ceftriaxone, cefixime syrup and tablet and azithromycin. These results indicate that most of antibiotic use at Mitra Sejati Hospital is included in the 90% DU segment, but routine monitoring is still needed to ensure the appropriateness of its use.